Calcul parallèle appliqué aux écoulements de fluides complexes - Digonnet, Hugues; Basset, Olivier; Silva, Luisa; Coupez, Thierry (European Journal of Computational Mechanics, 2007)
In this paper we present numerical simulations of complex fluid flows performed on a PC cluster. These simulations were possible thanks to a parallelization strategy that is transparent and efficient: each developer does not need to know a parallel programming library and its specific language. Instead, he uses purely SPMD tools to build their applications. Two examples are shown, as well as the computational results obtained for problems that need the resolution of linear Systems of over 7 million of unknowns.